Performance indicators related to women's health - Kaimi Pereira Costa; Cândido Simões Pires Neto (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to determine performance indicators related to women's health. Data were collected from 457 women living in the State of Parana, Brazil, classified according to age: 20-29 years (N=158), 30-39 years (N=171) and 40-49 years (N=128). The following variables were analyzed: height (m), body weight (kg), BMI, waist-hip ratio, abdominal strength (repetitions), flexibility (cm), and right and left hand grip strength (kgf). Descriptive statistics, one-factor ANOVA and the Tukey post-hoc test were used for statistical analysis (p ≤ 0.05). The results showed a significant difference (p ≤ 0.05) in all categories of the variables analyzed, except for right hand grip strength (good and excellent) at age 30-39 years and left hand grip strength at age 40-49 years. There was a higher incidence of inadequate BMI and waist-hip ratio and low abdominal strength among women aged 40-49 years. Low flexibility was more frequent in the 20-29 year group. The differences in right and left hand grip strength between age groups were small.